Book review of: Angebauer, Niklas; Blumenfeld, Jacob; Wesche, Tilo (Hrsg.) (2025): Umkämpftes Eigentum. Eine gesellschaftstheoretische Debatte - Hesse, Markus (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Book review.